Economic Viability as a Concept in Joint forest Management : a Case Study from the Bankura (North) Division, West Bengal - Deb, Sudeep Budhaditya (Indian Forester, 2009)
Joint Forest Management (JFM), the partnership between the Government Forest Department and forest - fringe community (organised through the Forest Protection Committees (FPCs)) towards Forest Protection, had its inception in the state of West Bengal and is considered to be most successful in this state. Bankura (North) Division, being part of the successful JFM zone, has some unique features like, diverse topographical configurations, availability of commercially viable minerals beneath the forests in some areas and regions, like Barjora, that have seen a recent spurt in industrialisation and urbanisation. All these features provided an exclusive opportunity to study the factors leading to the effectiveness of JFM, involving the FPCs. The study aimed at evaluating the effectiveness of JFM from the economic perspective, like the effect of the protection-linked direct incentives, impact of the market forces and the existence of demand for alternative use of forest land. Both the quantitative and the qualitative investigations were undertaken to this effect. In the quantitative study, some 80 FPCs were studied, based upon the presence of 11 - criteria chosen for the purpose. The results confirmed that the effect of protection - linked direct incentives, impact of market forces and existence of demand for alternative use do influence the effectiveness of FPCs. To augment the quantitative study, some 20 FPCs, showing somewhat unexpected results, were probed further in the qualitative study. The results, therein, augmented the findings of the quantitative study and also confirmed the existence of free - riders and the fact that the very JFM in the study area is in actuality a result of the choice of the economic rationale within the FPC community, rather than that of being motivated by the emotions attached to being a part of a peoples' movement, as is normally attributed to the JFM regime in south West Bengal.